The Framework and Statistical Methodology for Sugarcane Production in Thailand - Chaitip , Prasert; Chaiboonsri , Chukiat; Inluang, Fawikorn (Current Aspects in Business, Economics and Finance Vol. 6, 2022)
This chapter investigates the statistical features of technical efficiency (TE), which was evaluated using Data Envelopment Analysis in a panel data setting (Panel DEA) with data obtained from sugarcane farming households in major regions of Thailand. A Panel Bootstrap Method is used to determine the statistical precision of Panel Data Envelopment Analysis. An examination of scale efficiency reveals that for two ordinarily long years, the technical efficiency analysis of farm households involved in sugarcane production can be adopted for policy recommendation based on bootstrapping DEA panel data approaches because the mean of bootstrapping Panel DEA approach equal to the mean of DEA approach in the panel data setting in both 2008 and 2011 only.